Paikalliset latvuspeittävyysmallit beta-regressiolla - Korhonen, Lauri; Korhonen, Kari T.; Stenberg, Pauline; Maltamo, Matti; Rautiainen, Miina (Metsäntutkimuslaitos, 2007)
Seloste artikkelista: Korhonen, L., Korhonen, K.T., Stenberg, P., Maltamo M. & Rautiainen, M. 2007. Local models for forest canopy cover with beta regression. Silva Fennica 41(4): 671–685.
Tutkimusseloste